Anal Swab Examination of Salmonella in Typhoid Patients after Antibiotics Treatment - Prabandari, Anggraeni Sih; Ismail, Nor Isnida; Utami, Nataly Ayu (Global Health Science Group, 2024)
Thypoid is an endemic infectious disease in several countries caused by Salmonella thypi and Salmonella parathypi bacteria. These bacteria can be found in the blood, feces and urine of sufferers. Ciprofloxacin, Amoxicillin, Chloramphenicol and Ceftriaxone are commonly prescribed antibiotics in the treatment of thypoid. A stool examination to find the bacteria that causes thypoid can be used to evaluate the success of treatment and the patient's recovery rate. S. thypi Ag Rapid Test is an easy and fast method to detect the presence of thypoid bacteria. Objective: This study aims to detect the presence of thypoid bacteria in the feces of patients who receive antibiotic treatment on days 5, 10 and 15. Method: It was an observation research with a cross sectional approach. Samples in the form of anal swabs from 36 thypoid fever patients were taken on days 5, 10 and 15 after receiving antibiotic treatment. The examination uses S. thypi Ag Rapid Test. Results: A total of 27.8% of the samples showed positive results on the 5th day of examination, 22.2% were positive on the 10th day of examination and 11.1% of the samples were positive on the 15th day of the examination regardless of the type of antibiotic given. Conclusion: There was a decrease in the number of positive samples from day 5 to day 15, indicating improvement or recovery in some samples.